Improving the Articulation Ability of Children with Hearing Impairment Using Role Playing Method - Wina Try Saptari; Budi Susetyo; Iding Tarsidi (Journal of ICSAR, 2022)
Children with hearing impairment have difficulty conveying what they want to express by speaking because of speech and language development barriers, so they can only express it through speech in a minimal voice. This study aims to determine the effect of using role playing to improve the articulation ability of children with hearing impairment, on the grounds that conversations with friends during role playing can improve their expressive language skills (articulation skills to communicate). Research using role playing for children with hearing impairment to improve their articulation skills is successful because intensive oral communication exercises can make children train their lip muscles so that later they will get used to speaking/articulate when communicating with people who can hear. Researchers recommend role playing can be used as an effort to improve the articulation ability of children with hearing impairment.